Comparative Analysis of Different Control Strategies and Materials for a Community Microgrid - A Case Study - Pranto, Jubaer Akon; Kadir, Md Moin; Khan, Md. Yakub Ali (Peneliti Teknologi Teknik Indonesia, 2024)
The main objective of this study is to conduct a comparative analysis of various control strategies and materials used in the operation of community microgrids. An analysis that contrasts various methods for managing a microgrid's operations in a community context is called comparison research on control strategies for community microgrids. The study's objectives are to evaluate the benefits and drawbacks of various control systems and to pinpoint the best approach for maximizing the microgrid's performance and materials for microgrid. The study compares various control strategies, including islanded mode control, hybrid mode control, and grid-connected mode control. Advanced strategies that integrate economic dispatch with optimal power flow are also evaluated. A comparison is done taking into account variables including resilience, cost-effectiveness, efficiency, stability, and reliability. The findings provide valuable insights into the optimal control approach tailored to the specific needs of community microgrids, considering available resources, local energy consumption patterns, and other critical factors. The report also emphasizes the advantages of employing sophisticated control systems, including enhanced resilience and flexibility, increased cost-effectiveness, and improved integration with the main grid. In general, the comparative analysis of different control strategies for community micro-grids offers insightful knowledge to scholars, engineers, and decision-makers engaged in micro-grid design and operation, assisting in enhancing the efficiency and dependability of these systems for the good of communities.